2015
DOI: 10.1002/jsfa.7492
|View full text |Cite
|
Sign up to set email alerts
|

Selected chemical compounds in firm and mellow persimmon fruit before and after the drying process

Abstract: These results showed that the drying process improved the quality of persimmon products and extended their shelf life. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…‘Rojo Brillante’ than from ‘Triumph’. Other authors also reported gallic acid as the main phenolic compound in fresh as well as in dried persimmon from different cultivars . The amount of the other phenolic compounds also depended on the cultivar: in general, flour fractions from cv.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…‘Rojo Brillante’ than from ‘Triumph’. Other authors also reported gallic acid as the main phenolic compound in fresh as well as in dried persimmon from different cultivars . The amount of the other phenolic compounds also depended on the cultivar: in general, flour fractions from cv.…”
Section: Resultsmentioning
confidence: 88%
“…The differences observed between these studies and the current work could be due to the heat treatment applied to the co‐products to obtain the flours. Senica and colleagues reported than in dehydrated firm persimmon, the concentrations of citric, malic and tartaric acids decreased with heat treatment, although the fumaric acid content was less affected. Such differences may also be affected by the maturity stage, the ‘deastringency’ treatment and the type of sample (persimmon fruit vs. co‐product).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Exploratory studies of hot air-dried and sun-dried sliced persimmon products have been conducted by a number of groups (Cárcel, García-Pérez, Sanjuán, & Mulet, 2010;Igual, Castelló, Roda, & Ortolá, 2011;Karakasova, Babanovska-Milenkovska, Lazov, & Stojanova, 2013;Park et al, 2006;Senica, Veberic, Grabnar, Stampar, & Jakopic, 2016). However, of the more than 100 persimmon cultivars that exist, these studies have collectively involved only a small subset: 'Triumph' (Park et al, 2006), 'Rojo Brillante' (Cárcel et al, 2010;Igual et al, 2011), 'Tipo' (Senica et al, 2016), and an unspecified astringent cultivar (Karakasova et al, 2013). These studies included chemical analysis of the fruit, performed before and after drying.…”
mentioning
confidence: 99%
“…Most storage techniques require low temperatures, which are difficult to maintain throughout a distribution chain (Sagar and Kumar 2010). In addition to freezing, drying is the simplest procedure for preserving fruit (Senica et al 2016). Not only does it extend the shelf-life of fruit, but it retains the characteristics of natural products, reduces the costs of packing, storage and transportation, due to the reduced weight and volume of the product, and additionally inhibits the growth of micro-organisms (Wang and Xu 2007, Chauhan and Srivastava 2009, Sagar and Kumar 2010, Mundada et al 2010.…”
Section: Introductionmentioning
confidence: 99%